Determination of maximal oxygen consumption of Algerian soccer players during preseason - Abdelaziz, D.; Nadjib, A. (Journal of Physical Education and Sport, 2011)
The aim of this study was to assess the cardio-respiratory profile (VO2 max) of Algerian soccer players during preseason and compare VO2 max by competition level. Materials and Methods.- A total of 45 Algerian soccer players participated in the study, of which 22 were second division, 23 third division forwards with an average age of 23.13 ± 2.46 years; height 180, 67 ± 3, 54 cm; weight 80,35 ± 3,25 kg; body mass index 24,61± 0,38 kg/m2. In order to evaluate the VO2 max of players, the 20-m Multi Stage Shuttle Run Test (MST) protocol was used as recommended by (Leger et al., 1988). Results: of the total sample (n=45) with a general average of 57,38 ± 1,83 ml/kg/min, in which Second division sample (n=22) with a average of 58,28 ± 1,35 ml/kg/min had the highest VO2 max and third division sample (n=23) with a average of 56,53 ± 1,84 ml/kg/min. a statistically significant differences were found (P<0.05) between competition level. Conclusion: Results show that the Algerian second division football players tested have a normal VO2 max at the beginning of the preseason in comparison with the findings of other studies of international soccer players.